Mary and Lou and Rhoda and Ted : and all the brilliant minds who made The Mary Tyler Moore show a classic - Armstrong, Jennifer Keishin (Simon & Schuster, 2013)
The behind-the-scenes story of the making of the classic television series offers insight into how the influential show reflected changing American perspectives and was a first situation comedy to employ numerous women as writers and producers.